The Use of Illustrated Storybook Media in Increasing Early Childhood Creativity at RA An-Nuur Ratna Chaton Seputih Raman Lampung Tengah - Herlina; Romdiyah, Hidayatur (Jurnal Profesi Guru Indonesia, 2025)
This study investigated the use of picture story books as a tool to enhance creativity in early childhood education at RA An-Nuur Ratna Chaton Seputih Raman Lampung Tengah. This study aimed to explore how picture story books can stimulate children's imagination, improve their language skills, and foster social interaction, which ultimately contribute to the development of creativity. This study used a qualitative approach, observing and analyzing children's engagement, responses, and behaviors during and after storybook-related activities. Findings showed that the integration of picture story books into the learning process significantly increased children's enthusiasm and participation in classroom activities. In addition, children showed increased creative thinking, including imaginative play and problem-solving skills, while also showing improvements in language expression and social collaboration. The results showed that picture story books are an effective tool in supporting early childhood children's cognitive, emotional, and social development, emphasizing the importance of incorporating such resources into early childhood education to foster creativity and overall growth.